If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3G + 4) + -2g = 5(2g + -4) + 3 Reorder the terms: 7(4 + 3G) + -2g = 5(2g + -4) + 3 (4 * 7 + 3G * 7) + -2g = 5(2g + -4) + 3 (28 + 21G) + -2g = 5(2g + -4) + 3 Reorder the terms: 28 + 21G + -2g = 5(-4 + 2g) + 3 28 + 21G + -2g = (-4 * 5 + 2g * 5) + 3 28 + 21G + -2g = (-20 + 10g) + 3 Reorder the terms: 28 + 21G + -2g = -20 + 3 + 10g Combine like terms: -20 + 3 = -17 28 + 21G + -2g = -17 + 10g Solving 28 + 21G + -2g = -17 + 10g Solving for variable 'G'. Move all terms containing G to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + 21G + -28 + -2g = -17 + -28 + 10g Reorder the terms: 28 + -28 + 21G + -2g = -17 + -28 + 10g Combine like terms: 28 + -28 = 0 0 + 21G + -2g = -17 + -28 + 10g 21G + -2g = -17 + -28 + 10g Combine like terms: -17 + -28 = -45 21G + -2g = -45 + 10g Add '2g' to each side of the equation. 21G + -2g + 2g = -45 + 10g + 2g Combine like terms: -2g + 2g = 0 21G + 0 = -45 + 10g + 2g 21G = -45 + 10g + 2g Combine like terms: 10g + 2g = 12g 21G = -45 + 12g Divide each side by '21'. G = -2.142857143 + 0.5714285714g Simplifying G = -2.142857143 + 0.5714285714g
| 5x-22=3x-36 | | 2x^3-65x-75=0 | | [1/4(1-5)] | | 5k+2=-8 | | r+5.73=10 | | 1/2x-7=1/3(x-12) | | 5d-6a+7d+3a-2+8a+7= | | -(2x-1)+x=7 | | 10.5=-1.5-1.5x | | X=102+18x | | 5y+13=1-3 | | -5y+9=-8y-6 | | 12x+9=6x-15 | | 33=2v+13 | | F=MGH | | X-88=9(2x+3)-13 | | 5x^3-4x^2+8=0 | | 4x^2-15x+18=-2x+8 | | 5ad-6a+7d+3a-2+8a+7= | | y/3.3=3 | | x^2-12x+20=-2x+4 | | X-22=7(2x+3)-17 | | X*lnx+1=0 | | x^2+6x+33=-7x-3 | | 3(6+b)(2+b)= | | -5(5n+f)=15 | | 6x-5x-15=22 | | -7(x+9)+70=11-8x | | 3x^2-10+7x=180 | | a-2.5=5.5 | | 5h+3s=96 | | -28.50-0.75x=36.75 |